Sastra Dalam Pendidikan Berkarakter : Mewujudkan Pembelajaran Yang Berarti - Marcelinus Widananta (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Character education aims to form better student character. Currently, character education is a major concern in the field of education. This is because awareness of human sensitivity and sensitivity to surrounding phenomena is decreasing. Integrating teaching literature with character education is one smart solution to instill character values ​​from an early age to students. Through literature, students can be routinely introduced to feelings, thoughts, and spiritual development, which will eventually form good behavior and habits in them. Teaching literature, either directly or indirectly, will help students increase their understanding of traditions in human life, increase their sensitivity to personal and social issues, and increase their knowledge of scientific and technological concepts.